Physics I for dummies - Holzner, Steven (Hoboken, NJ : Wiley Publishing, Inc., 2011)
Overview: The fun and easy way to get up to speed on the basic concepts of physics For high school and undergraduate students alike, physics classes are recommended or required courses for a wide variety of majors, and continue to be a challenging and often confusing course. Physics I For Dummies tracks specifically to an introductory course and, keeping with the traditionally easy-to-follow Dummies style, teaches you the basic principles and formulas in a clear and concise manner, proving that you don't have to be Einstein to understand physics!: Explains the basic principles in a simple, clear, and entertaining fashion; New edition includes updated examples and explanations, as well as the newest discoveries in the field; Contains the newest teaching techniques; If just thinking about the laws of physics makes your head spin, this hands-on, friendly guide gets you out of the black hole and sheds light on this often-intimidating subject.
Part 3: -- Manifesting The Energy To Work: -- Getting some work out of physics: -- Looking for work -- Working on measurement systems -- Pushing your weight: applying force in the direction of movement -- Using a tow rope: applying at an angle -- Negative work: applying force opposite the direction of motion -- Making a move: kinetic energy -- Work-energy theorem: turning work into kinetic energy -- Using the kinetic energy equation -- Calculating changes in kinetic energy by using net force -- Energy in the bank: potential energy -- To new heights: gaining potential energy by working against gravity -- Achieving your potential: converting potential energy into kinetic energy -- Choose your path: conservative versus nonconservative forces -- Keeping the energy up: the conservation of mechanical energy -- Shifting between kinetic and potential energy -- Mechanical-energy balance: finding velocity and height -- Powering up: the rate of doing work -- Using common units of power -- Doing alternate calculations of power -- Putting objects in motion: momentum and impulse: -- Looking at the impact of impulse -- Gathering momentum -- Impulse-monentum theorem: relating -- Impulse and momentum -- Shooting pool: finding force from impulse and momentum -- Singing in the rain: an impulsive activity -- When objects go bonk: conserving momentum -- Deriving the conservation formula -- Finding velocity with the conservation of momentum -- Finding firing velocity with the conservation of momentum -- When worlds (or cars) collide: elastic and ineleastic collisions -- Determining whether a collision is elastic -- Colliding elastically along a line -- Colliding elastically in two dimensions -- Winding up with angular kinetics: -- Going from linear to rotational motion -- Understanding tangential motion -- Finding tangential velocity -- Finding tangential acceleration -- Finding centripetal acceleration -- Applying vectors to rotation -- Calculating angular velocity -- Figuring angular acceleration -- Doing the twist: torque -- Mapping out the torque equation -- Understanding lever arms -- Figuring out the torque generated -- Recognizing the torque is a vector -- Spinning at constant velocity: rotational equilibrium -- Determining how much weight Hercules can lift -- Hanging a flag: a rotational equilibrium problem -- Ladder safety: introducing friction into rotational equilibrium -- Round and round with rotational dynamics: -- Rolling up Newton's second law into angular motion -- Switching force to torque -- Converting tangential acceleration to angular acceleration -- Factoring in the moment of inertia -- Moments of inertia: looking into mass distribution -- DVD players and torque: a spinning-disk inertia example -- Angular acceleration and torque: a pulley inertia example -- Wrapping your head around rotational work and kinetic energy -- Putting a new spin on work -- Moving along with rotational kinetic energy -- Let's roll! Finding rotational kinetic energy on a ramp -- Can't stop this: angular momentum -- Conserving angular momentum -- Satellite orbits: a conservation-of-angular momentum example -- Springs'n'things: simple harmonic motion: -- Bouncing back with Hooke's law -- Stretching and compressing springs -- Pushing or pulling back: the spring's restoring force -- Getting around to simple harmonic motion -- Around equilibrium: examining horizontal and vertical springs -- Catching the wave: a sine of simple harmonic motion -- Finding the angular frequency of a mass on a spring -- Factoring energy into simple harmonic motion -- Swinging with pendulums -- Part 5: -- Laying Down The Laws Of Thermodynamics: -- Turning up the heat with thermodynamics: -- Measuring temperature -- Fahrenheit and Celsius: working in degrees -- Zeroing in on the Kelvin scale -- Heat is on: thermal expansion -- Linear expansion: getting longer -- Volume expansion: taking up more space -- Heat: going with the flow (of thermal energy) -- Getting specific with temperature changes -- Just a new phase: adding heat without changing temperature -- Here, take my coat: how heat is transferred: -- Convection: letting the heat flow -- Hot fluid rises: putting fluid in motion with natural convection -- Controlling the flow with forced convection -- Too hot to handle: getting in touch with conduction -- Finding the conduction equation -- Considering conductors and insulators -- Radiation: riding the (electromagnetic) wave -- Mutual radiation: giving and receiving heat -- Blackbodies: absorbing and reflecting radiation -- In the best of all possible worlds: the ideal gas law: -- Digging into molecules and moles with Avogadro's number -- Relating pressure, volume, and temperature with the ideal gas law -- Forging the ideal gas law -- Working with standard temperature and pressure -- Breathing problem: checking your oxygen -- Boyle's and Charles's laws: alternative expressions of the ideal gas law -- Tracking ideal gas molecules with the kinetic energy formula -- Predicting air molecule speed -- Calculating kinetic energy in an ideal gas -- Heat and work: the laws of thermodynamics: -- Thermal equilibrium: getting temperature with the Zeroth law -- Conserving energy: the first law of thermodynamics -- Calculating with conservation of energy -- Staying constant: isobaric, isochoric, isothermal, and adiabatic processes -- Flowing from hot to cold: the second law of thermodynamics -- Heat engines: putting heat to work -- Limiting efficiency: Carnot says you can't have it all -- Going against the flow with heat pumps -- Going cold: the third (and absolute last) law of thermodynamics -- Part 5: -- Part Of Tens: -- Ten physics heroes: -- Galileo Galilei -- Robert Hooke -- Sir Isaac Newton -- Benjamin Franklin -- Charles-Augustin de Coulomb -- Amedeo Avogadro -- Nicolas Leonard Sadi Carnot -- James Prescott Joule -- William Thomson (Lord Kelvin) -- Albert Einstein -- Ten wild physics theories: -- You can measure a smallest distance -- There may be a smallest time -- Heisenberg says you can't be certain -- Black holes don't let light out -- Gravity curves space -- Matter and antimatter destroy each other -- Supernovas are the most powerful explosions -- Universe starts with the big bang and ends with the gnab gib -- Microwave ovens are hot physics -- Is the universe made to measure? -- Glossary -- Index.
Includes index.
Keywords: Physics; Nonfiction